2017
DOI: 10.1101/107383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of DNA2 nuclease as a therapeutic strategy targeting replication stress in cancer cells

Abstract: Replication stress is a characteristic feature of cancer cells, which is resulted from sustained proliferative signaling induced by activation of oncogenes or loss of tumor suppressors. In cancer cells, oncogene-induced replication stress manifests as replication-associated lesions, predominantly double-strand DNA breaks (DSBs). An essential mechanism utilized by cells to repair replication-associated DSBs is homologous recombination (HR). In order to overcome replication stress and survive, cancer cells often… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…We observed no inhibition of yeast DNA2 by FANCD2, even at great molar excess FANCD2, on either the forked substrate or the reversed fork substrate (Figure S2D and S2E). Note that yDNA2 is more active than hDNA2, as also reported by others (Kumar et al, 2017), accounting for the concentrations used. The lack of inhibition of yeast DNA2 by FANCD2 supports, though it does not prove, that inhibition of hDNA2 by FANCD2 involves a species-specific and therefore likely a physiologically significant protein/protein interaction.…”
Section: Resultssupporting
confidence: 79%
“…We observed no inhibition of yeast DNA2 by FANCD2, even at great molar excess FANCD2, on either the forked substrate or the reversed fork substrate (Figure S2D and S2E). Note that yDNA2 is more active than hDNA2, as also reported by others (Kumar et al, 2017), accounting for the concentrations used. The lack of inhibition of yeast DNA2 by FANCD2 supports, though it does not prove, that inhibition of hDNA2 by FANCD2 involves a species-specific and therefore likely a physiologically significant protein/protein interaction.…”
Section: Resultssupporting
confidence: 79%
“…Regulation of Dna2-dependent resection seems to be more complex than Exo1, which appears to only require DNA ends not protected by Ku. Furthermore, understanding the function of Dna2 at DSBs has been challenging because DNA2 is an essential gene involved in Okazaki fragment processing and cannot be deleted (21)(22)(23)(24)(25). Earlier work showed that the lethality of dna2Δ can be suppressed by disruption of PIF1 helicase and that the frequency of 5 0 resection decreased at a DSB in dna2Δ pif1-m2 mutants (19,26).…”
mentioning
confidence: 99%
“…To test this hypothesis, we used the specific DNA2 activity inhibitor NSC105808 (NSC) 16 . We confirmed that targeting DNA2 activity overcame resistance to ILF2 ASOs and induced MM cell death in vitro (Supplementary Fig.…”
Section: Dna2 Is Essential For Maintaining MM Cells' Survival After D...mentioning
confidence: 99%